(untitled) (REMUNOM, 2024)
Benign prostatic hyperplasia (BPH) is understood as a disease that mainly affects men over the age of 40, with aging being the main risk factor. In this way, benign prostatic hyperplasia can lead to interference in the quality of life of the sufferer, as its clinical picture mainly presents deficiencies in the functioning of the lower urinary tract. This study will use the quantitative, retrospective documentary method through port workers at Fundação Hospitalar São Lucas, in the state of Paraná, in the year 2020 to 2024, to survey the different types of treatment for patients with Benign Prostatic Hyperplasia. Therefore, the research’s mission is to highlight the importance of correct management of the disease, as well as knowledge of the different techniques and forms of treatment.